Pengaruh Penerapan Standar Akuntansi Pemerintah Berbasis Akrual, Sistem Pengendalian Intern dan Kualitas Laporan Keuangan terhadap Akuntabilitas Kinerja Inspektorat Kabupaten Bengkulu Tengah - Saniya, Tika; Yulianasari, Nina; Herawati, Helmi (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
Public sector organizations are expected to uphold high standards of transparency, accountability, and good governance. In Indonesia, government institutions are required to implement accrual-based accounting systems and internal controls to ensure the quality and reliability of financial reporting. However, questions remain regarding how effectively these elements contribute to performance accountability at the regional level. This study aimed to determine whether the application of accrual-based Government Accounting Standards (SAP), internal control systems (SPI), and the quality of financial reports affect performance accountability at the Inspectorate of Central Bengkulu Regency, both partially and simultaneously. The research employed a quantitative approach, collecting data through questionnaires distributed to 30 employees who met purposive sampling criteria. Responses were measured using a Likert scale. Data analysis was conducted using multiple linear regression with SPSS version 26.0. Prior to hypothesis testing, several classical assumption tests were performed, including validity and reliability tests, as well as normality, multicollinearity, and heteroscedasticity tests. The results revealed that the application of accrual-based SAP, internal control systems, and the quality of financial statements each have a significant and positive impact on performance accountability. These findings underscore the importance of implementing sound financial and administrative practices to improve transparency, efficiency, and trust in government operations, reinforcing the principles of good governance.